2018
DOI: 10.1186/s12968-018-0430-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive differentiation of idiopathic inflammatory myopathy with cardiac involvement from acute viral myocarditis using cardiovascular magnetic resonance imaging T1 and T2 mapping

Abstract: BackgroundIdiopathic inflammatory myopathy (IIM) is a group of autoimmune diseases with systemic myositis which may involve the myocardium. Cardiac involvement in IIM, although often subclinical, may mimic clinical manifestations of acute viral myocarditis (AVM). Our aim was to investigate the usefulness of the combined analysis of cardiovascular magnetic resonance (CMR) T1 and T2 mapping parameters measured both in the myocardium and in the thoracic skeletal muscles to differentiate AVM from IIM cardiac invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
6
39
0
1
Order By: Relevance
“…The uncertain conclusions in previous studies may be attributable to differences in patient selection, approaches used to evaluate cardiac abnormalities, different follow-up intervals, and the insufficient sample sizes. In the present study, we found that newly diagnosed IIM patients had significantly elevated T1, T2, and ECV values on both myocardium and skeletal muscles, which are consistent with the findings of previous studies [10,12]. In addition, we also demonstrated for the first time that multiparametric CMR can detect dynamic changes in both myocardial and skeletal tissue characteristics after effective treatment.…”
Section: Abbreviationssupporting
confidence: 93%
See 3 more Smart Citations
“…The uncertain conclusions in previous studies may be attributable to differences in patient selection, approaches used to evaluate cardiac abnormalities, different follow-up intervals, and the insufficient sample sizes. In the present study, we found that newly diagnosed IIM patients had significantly elevated T1, T2, and ECV values on both myocardium and skeletal muscles, which are consistent with the findings of previous studies [10,12]. In addition, we also demonstrated for the first time that multiparametric CMR can detect dynamic changes in both myocardial and skeletal tissue characteristics after effective treatment.…”
Section: Abbreviationssupporting
confidence: 93%
“…In the present study, newly diagnosed IIM patients showed significantly elevated T1, T2, and ECV values in comparison with normal controls, and these findings are consistent with recent CMR studies of IIM patients [10,12]. We also found that the myocardial native T1, T2 and ECV values were significantly correlated with the NT-proBNP level, which may suggest that.…”
Section: Myocardial and Skeletal Muscles Involvement In Iimsupporting
confidence: 92%
See 2 more Smart Citations
“…2 and 9), and on the other hand, detection of ongoing myocardial inflammation requiring further clinical evaluation [33,38]. Myocardial involvement in idiopathic inflammatory myopathy cannot be differentiated from acute myocarditis by native T1 or ECV mapping but possibly by the additional evaluation of skeletal muscle T1 and ECV [39]. The association of myocardial native T1 or ECV estimates with diffuse myocardial fibrosis in systemic inflammatory diseases like sarcoidosis, systemic lupus erythematosus, rheumatoid arthritis, or systemic sclerosis is limited (Table 1), as increased native T1 and ECV values in these diseases reflect "myocardial edema-related" disease activity scores rather than "fibrosis-related" disease progression [2,[40][41][42].…”
Section: Normal Left Ventricular Configurationmentioning
confidence: 99%